The Relation between Islam and The State from Islamic Education Perspective:Al-Banna, Haikal and Raziq Thought - Nanang Hasan Susanto; Mudjahirin Thohir; Abdul Wahib; Abdul Mukhlis; Yayan Rahayani (Jurnal Penelitian, 2021)
This research discusses the relation between Islam and the State among Muslim scholars. Many discuss the relation between Islam and the State from Sharia and historical viewpoints. However, this study examines the relation from education standpoint. The literature research looks at academic publications from prominent Muslim scholars around the world. This research asserts that the study on relation between Islam dan the State can be divided into three main categories: integrative, substantive and secular. In relation to education, those studies reveal that educational institutions attempt to align their teaching ideology with the ideology of its founder or stakeholders. Despite their significant differences, all Muslim scholars derive their thought and discussion from thelogical foundation of Al-Qur’an and Hadith. They also seem to show a common ground in defining Islamic Education. Nevertheless, Islamic education institutions present various views on teaching the ideology in relation between Islam and the State, from moderate teaching to radical teaching or understanding.